Antibiotic Resistance And Plasmid Contents Of Salmonella Serotypes Isolated From Raw Milk: Khilud K.Nazal, Najim H.Najim , Mohammed A. Hassem - Nazal, Khilud K. (The Iraqi Journal of Veterinary Medicine, 2007)
This study lasted for eight months .The main objectives of the study wereto identify the main sources of raw milk pollution with Salmonella with aspecial emphasis on determination of their serotypes. The relationship betweentheir resistance to antibiotics and their plasmide contents were also studied.Six hundred raw milk samples collected randomly at weekly intervals where thefirst (300) samples were from the individual milk cans (50 Kg each) at theproducers homes in Abu-Ghraib village while the second (300) samples werecollected from the scale bulk tanks (2 tons) inside the milk reception andcollection center at the same village.In addition to that (200) swabs were taken from four different location (50swabs for each) namely: the teats, milkers hands, the inner surface of the milkcans and the sedimemts that were precipitated at the bottom of the scale bulktank.Data revealed that 5% of the milk cans and 7% of the scale bulk tank werecontaminated with Salmonella besides the percentage of the Salmonella isolatesfrom different swabs location were as 10% , 30% , 8% and 52% out of the teats,inner surface of milk cans, milker’s hands and sediments of the bulk tanksrespectively .Seven serotypes of Salmonella were identified from both milk samples andswabs including S. typhimurium 40 %, S. anatum 26.67%, S. Kottbus 13.33 %,S. infantis 6.67%, S. dublin6.67%, S. java 3.33% and S. typhi 3.33%.Antibiotic sensitivity test for different antibiotics revealed that mostSalmonella isolates were resistant to two antibiotics where (36.66%)of theisolates were resistant to Sulphamethazol, (16.66%)were resistant to tetracycline, (10%) were resistant to Streptomycin and (3.33%) were resistant to each ofChloramphenicol , Kanamycin and Ampicillin.The extraction of the DNA-plsmide revealed that seven out of ten isolatescontained large, individual plasmids size of (50-70) Killo Base (KB) while theothers three isolate were free from such plamid.